2021
DOI: 10.1016/j.sjbs.2021.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal fungi induced activation of tomato defense system mitigates Fusarium wilt stress

Abstract: The fungus Fusarium oxysporum f. sp. lycopersici (FOL) is known to cause vascular wilt on tomato almost over the world. Inoculation of FOL reduced plant growth and increased wilt of tomato. The following study examined the possible role of arbuscular mycorrhizal fungi (AMF) consortium comprising of Rhizophagus intraradices , Funneliformis mosseae and Claroideoglomus etunicatum against FOL in tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The growth improvement is also probably due to pre-inoculation [77]. The increase in colonization will sustain a better resistance to biotic and abiotic stresses [62,[78][79][80]. However, there are genotypes with low inoculum acceptance rates that correlate with low mycorrhizal potential.…”
Section: Discussionmentioning
confidence: 99%
“…The growth improvement is also probably due to pre-inoculation [77]. The increase in colonization will sustain a better resistance to biotic and abiotic stresses [62,[78][79][80]. However, there are genotypes with low inoculum acceptance rates that correlate with low mycorrhizal potential.…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with 100 µM FA reduced APX and CAT activities in tobacco cell suspension culture after 24 h (Jiao et al 2014 ). Similarly, Hashem et al ( 2021 ) infected tomato plants with the FA-producing fungus F. oxysporum and then observed that the activities of the enzymes DHAR and GPX decreased, while the enzymatic activities of SOD and APX increased as a result of the fungal infection. Conversely, higher SOD (after 48 h) and CAT (after 12 and 24 h) activities were significantly increased after FA treatment (2 × 10 −4 M) in cell suspensions of tomato plants (Kuźniak 2001 ).…”
Section: Fa-induced Changes In Enzymatic and Non-enzymatic Antioxidantsmentioning
confidence: 97%
“…ROS accumulation upon FA exposure induces both enzymatic and non-enzymatic antioxidants (Antić et al 2020 ; Dong et al 2014 ). These ROS-scavenging antioxidants include superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), peroxidase (POD), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione S-transferase (GST), dehydroascorbate reductase (DHAR), glutathione (GSH), ascorbate (ASC) and phenolic compounds (Sharma et al 2022 ; Hashem et al 2021 ; Gupta et al 2018 ; Sapko et al 2011 ; Foyer and Noctor 2009 ). These antioxidants are responsible for cell protection and defence against toxic levels of overproduced ROS following fungal attacks (Gill and Tuteja 2010 ).…”
Section: Fa-induced Changes In Enzymatic and Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…For example, Fusarium oxysporum is the cause of vascular wilt in tomato. Tomato plants inoculated with AMF are less suceptible to wilt (Hashem et al 2021). Parasitism of Trifolium pratense L. by Cuscuta australis R. Br.…”
Section: Plant-microorganism Interactionsmentioning
confidence: 99%
“…Tomato plants inoculated with AMF are less suceptible to wilt (Hashem et al . 2021). Parasitism of Trifolium pratense L. by Cuscuta australis R. Br.…”
Section: Mechanisms Of Allelopathy and Allelobiosismentioning
confidence: 99%